Association of the polymorphism of the Toll‐like receptor (TLR)‐3 and TLR‐9 genes with hepatitis C virus‐specific cell‐mediated immunity outcomes among Egyptian health‐care workers. (2nd October 2020) - Abdelwahab, S. F.; Hamdy, S.; Osman, A. M.; Zakaria, Z. A.; Galal, I.; Sobhy, M.; Hashem, M.; Allam, W. R.; Abdel‐Samiee, M.; Rewisha, E.; Waked, I.
Summary: Variations in the immune response could explain resistance to hepatitis C virus (HCV) infection. Toll‐like receptor gene (TLR)‐3 is an innate detector of dsRNA viruses, and the TLR‐9 gene recognizes bacterial and viral unmethylated cytosine–phosphate–guanosine (CpG) motifs. We previously reported that the TLR‐3.rs3775290 CC genotype was associated with HCV chronicity and that the TLR‐9 gene played no major role in this infection. This study identified the role of TLR‐3.rs3775290 (c.1377C/T), TLR‐9.rs5743836 (−1237T→C) and TLR‐9.rs352140 (G2848A) gene polymorphisms in predicting the outcome of HCV‐specific cell‐mediated immunity (CMI) among Egyptian health‐care workers (HCWs). We enrolled 265 HCWs in this study and divided them into four groups. Group 1: 140 seronegative‐aviraemic HCWs; group 2: 20 seronegative‐viraemic HCWs; group 3: 35 subjects with spontaneously resolved HCV infection; and group 4: 70 chronic HCV HCWs (patients). All subjects were genotyped by polymerase chain reaction–restriction fragment length polymorphism (PCR‐RFLP) analysis for the TLR‐3.rs3775290, TLR‐9.rs5743836 and TLR‐9.rs352140 single nucleotide polymorphisms (SNPs). We also quantified HCV‐specific CMI in the four groups using an interferon (IFN)‐γ enzyme‐linked immunospot (ELISPOT) assay in response to nine HCV genotype 4a, overlapping 15mer peptide pools covering the whole viral genome. No statistically significant difference was found between CMI‐responding subjects with different HCV states and TLR‐3.rs3775290 or TLR‐9.rs352140 genotypes. However, there was a significant relationship between the outcome of the HCV‐specific CMI and the TLR‐9.rs5743836 genotype among the responding subjects ( P = 0·005) and the chronic HCV patients ( P = 0·044). In conclusion, TLR‐9.rs5743836 SNP, but not TLR‐3.rs3775290 or TLR‐9.rs352140 genotypes, could predict the outcome of HCV‐specific CMI responses among Egyptians infected with genotype‐4. Abstract : We previously reported that TLR3.rs3775290 'CC' genotype was associated with HCV chronicity, while TLR9 gene played no role in this infection. Herein, we show a significant association between the outcome of the HCV‐specific cell‐mediated immune (CMI) response and TLR9.rs5743836 genotype among the total responding subjects with different HCV states (p=0.005) and among the chronic HCV patients (p=0.044). We conclude that TLR9.rs5743836 SNP; but not TLR3.rs3775290 or TLR9.rs352140 genotypes; could predict the outcome of HCV‐specific CMI responses among HCV genotype‐4‐infected Egyptians.